2012
DOI: 10.4103/0019-5413.93686
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis of hip in children: A retrospective analysis

Abstract: Background:Tuberculosis (TB) of hip constitutes nearly 15% of all cases of osteoarticular tuberculosis. We report a retrospective study carried out on 43 children with hip TB.Materials and Methods:Forty-three children of TB hip treated between 1971 and 2000 were analysed. Twenty-four children of the early series were treated with streptomycin (S), isoniazid (H) and PAS (Pa) for 18 months (3HPaS, 15 HPa), while 19 children in the later series were treated with isoniazid (H), rifampicin (R) and ethambutol (E) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…Traveling, mortar pestle and atrophic types had poorer results. In another pediatric series of 43 children by Moon et al ., results were described as excellent to good in 73%, fair in 18% and poor in 9% respectively 7. Poor results were obtained with protrusio acetabuli and mortar pestle types in this series.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Traveling, mortar pestle and atrophic types had poorer results. In another pediatric series of 43 children by Moon et al ., results were described as excellent to good in 73%, fair in 18% and poor in 9% respectively 7. Poor results were obtained with protrusio acetabuli and mortar pestle types in this series.…”
Section: Discussionmentioning
confidence: 52%
“…The exact proportion of tubercular hip affection in the pediatric age group is not known but the disease is rare. There is a paucity of literature regarding osteoarticular tuberculosis of hip in children with only few dedicated series available in recent indexed English literature and probably none from the Indian subcontinent 67. Thus, the clinicoradiological course in osteoarticular tuberculosis of hip following modern anti tubercular chemotherapy is scantly studied 67.…”
Section: Discussionmentioning
confidence: 99%
“…Recommends early rehabilitation regimen for ambulation as it boosted the patients’ confidence and activity level. 22 In addition to ATT, nutritional supplementation and traction, the specific treatment depends upon the stage of involvement at the time of diagnosis.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…2,20 A number of confirmed BCG-induced osteomyelitis cases have been reported from Europe and Asia. 5,14 However, to the best of the authors' knowledge, the current patient is believed to be the first confirmed case of BCG-induced TB hip osteomyelitis from Oman.…”
Section: 2mentioning
confidence: 99%
“…In paediatric cases, treatment strategies are primarily focused towards preserving anatomy, joint mobility and growth plates. 1,2,20,23 First-line anti-TB agents include isoniazid, rifampicin, streptomycin, pyrazinamide and ethambutol. A failure to respond to these medications may warrant the use of second-line agents including capreomycin, kanamycin, ethionamide, cycloserine, and paraaminosalicylic acid.…”
Section: 2mentioning
confidence: 99%